Annual cycles of deep‐ocean biogeochemical export fluxes in subtropical and subantarctic waters, southwest Pacific Ocean. Issue 4 (9th April 2016) - Nodder, Scott D.; Chiswell, Stephen M.; Northcote, Lisa C.
Abstract: The annual cycles of particle fluxes derived from moored sediment trap data collected during 2000–2012 in subtropical (STW) and subantarctic waters (SAW) east of New Zealand are presented. These observations are the most comprehensive export flux time series from temperate Southern Hemisphere latitudes to date. With high levels of variability, fluxes in SAW were markedly lower than in STW, reflecting the picophytoplankton‐dominated communities in the iron‐limited, high nutrient‐low chlorophyll SAW. Austral spring chlorophyll blooms in surface STW were near synchronous with elevated fluxes of bio‐siliceous, carbonate, and organic carbon‐rich materials to the deep ocean, probably facilitated by diatom and/or coccolithophorid sedimentation. Lithogenic fluxes were also high in STW, compared to SAW, reflecting proximity to the New Zealand landmass. In contrast, the highest biogenic fluxes in SAW occurred in spring when surface chlorophyll concentrations were low, while highest annual chlorophyll concentrations were in summer with no associated flux increase. We hypothesize that the high spring export in SAW results from subsurface chlorophyll accumulation that is not evident from remote‐sensing satellites. This material was also rich in biogenic silica, perhaps related to the preferential export of diatoms and other silica‐producing organisms, such as silicoflagellates and radiolarians. Organic carbon fluxes in STW are similar to that of other mesotrophic to oligotrophic waters (∼6–7 mg C m −2 d −1 ), whereas export from SAW is below the global average (∼3 mg C m −2 d −1 ). Regional differences in flux across the SW Pacific and Tasman region reflect variations in physical processes and ecosystem structure and function. Key Points: Sediment traps were deployed for 11 years in subtropical (STW) and subantarctic (SAW) waters In STW, organic carbon and bio‐siliceous fluxes coupled to spring blooms but lag autumn production Fluxes uncoupled from summer SAW biomass, highest in spring coincident with low surface chlorophyll